Local impedance characteristics and advanced mapping capabilities to better understand pulmonary veins reconnections during repeat AF ablation procedures: insight from the CHARISMA registry. (14th October 2021) - Segreti, L; Maggio, R; Bencardino, G; Izzo, G; De Lucia, R; Notaristefano, F; Ricciardi, G; Rossi, P; Giannotti Santoro, M; Ferraro, A; Perna, F; Solimene, F; et al.
Abstract: Background: Detailed characterization of pulmonary veins (PV) reconnection during repeat AF ablation through high-density mapping (HDM) and local impedance (LI) algorithm is still lacking. Purpose: We aimed to characterize PV gaps and underlying electrical activity during and after ablation of PVs in AF patients (pts). Methods: Consecutive patients (pts) undergoing redo AF ablation from the CHARISMA registry with complete characterization of PV gaps (PVG) at 8 Italian centers were included. Rhythmia mapping system was used to map the left atrium and PVs before and after ablation. LI characteristics were collected through a RF ablation catheter equipped with a dedicated LI algorithm (DirectSense). A novel map analysis tool (Lumipoint) that automatically identifies split potentials and continuous activation was used sequentially on each PV component, in order to better assess PVG. Each PVG was characterized in terms of LI and its variations during the procedure. Ablation endpoint was PVI as assessed by entrance and exit block. Results: Fifty PVGs were automatically identified through the Lumipoint tool in 23 cases, mostly at anterior sites (21, 42%), followed by posterior (15, 30%) and carina (10, 20%) sites. One PVG was identified in 7 (28%) pts, 2 gaps in 10 (43.5%) pts and >2 gaps in 6 (26.1%) pts. The mean LI at PVG sites was 111.3±12Ω prior to ablation: it was significantly higher than LI at scar tissue closer to PVG (99.3±8Ω, p<0.0001) but was significantly lower than LI at healthy tissue (120.8±11Ω, p=0.0015). The mean linear extension of PVGs detected through Lumipoint was significantly lower than the one recognized through voltage map (11.5±8 mm vs 13.3±9 mm, p=0.01) whereas was comparable to the one identified through conventional activation map (11.8±7 mm, p=0.1161 vs Lumipoint). Complete identification of the whole area of PVG was achieved in 31 (62%) and 42 (84%) cases through voltage and activation map, respectively whereas the identification was only partial in 18 (36%) and 7 (14%) cases, respectively. In 1 case both voltage and activation map failed to identify a PVG. No complications during the procedures were reported. All PVs were successfully isolated in all study pts. Conclusion: Advanced mapping capabilities were useful to pinpoint the search for PVGs, enabling a more targeted ablation approach vs relying on voltage mapping. LI values correlated well with PVGs characteristics and they significantly differ from both scar and healthy tissue. Funding Acknowledgement: Type of funding sources: None.